A fresh look at sports PSM-systems - Savostyanov, Vladimir; Kobelev, Alexander; Govorin, Anton (Journal of electrical bioimpedance, 2023)
The aim of the proposed study is to reveal the correlations between the dynamics of Respiratory Rate (RR) and Heart Rate (HR) during intermittent physical work at maximum power on a cycle ergometer. The stage of investigating the General functional athlete readiness (GFAR) was conducted using the sports standard “R-Engine” and the cycle ergometer in 16 volunteers (10 men, 6 women) whose average age was 21±1.17 years. To determine the athletic potential of the volunteers in this study, we used our own Coefficient of Anaerobic Capacity (CANAC Q, beats). Continuous registration of the heart rate and respiratory rate of volunteers in the maximum power sports test was performed by the “RheoCardioMonitor” system with a module of the athlete functional readiness based on the method of Transthoracic electrical impedance rheography (TEIRG). The degree of correlation of functional indicators (M, HRM, GFAR) with CANAC Q in all experimental series of the study group as a whole (n=80) was at a very high level, which confirmed the effectiveness of using the Coefficient of Anaerobic Capacity (CANAC Q) in assessing the general functional athlete readiness of the volunteers. CANAC Q is measured in “beats” of the heart and is recorded very accurately using the method of transthoracic electrical impedance rheography (TEIRG). For this reason, as a promising sports PSM-system, CANAC Q can replace the methods for determining the functional athlete readiness by blood lactate concentration and maximum oxygen consumption.